Peran Mahasiswa Universitas Sultan Ageng Tirtayasa dalam Mendorong Perekonomian UMKM di Kota Serang : (Sebuah Analisis Terhadap Kontribusi dan Tantangan) - Vera Maria; Selvia Laelatul Istianah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
One of the most common economic activities in the community is micro, small, and medium enterprises (MSMEs). These businesses are known for being relatively easy to develop and have the potential to strengthen a country's economy. As a source of income for most people, MSMEs are often their economic footing. Furthermore, MSMEs have the potential to compete with other businesses on an international level if they are continuously strengthened. If this is successfully achieved, it will provide a significant boost to national economic growth and support the stability of the country as a whole. The purpose of this research is to collect information about the role of contributions and obstacles faced by UNTIRTA students in an effort to encourage the economic development of MSMEs in Serang City. The research was conducted through a descriptive analysis method with a qualitative approach. To collect data, the author employed both literature study techniques and in-depth interview techniques with UNTIRTA students. The results of this study indicate that UNTIRTA students play a significant role in driving the MSME economy in Serang City. UNTIRTA students can assist in raising public awareness about the role and potential of MSMEs in Serang City. Nevertheless, further endeavors are necessary to enhance students' capacity and accessibility to requisite resources, as well as to reinforce collaboration between educational institutions, the government, and MSME stakeholders. It is anticipated that a more conducive environment for the growth and sustainability of MSMEs in Serang City can be created through close collaboration between students, educational institutions, local government, and MSME players.